2015
DOI: 10.1080/00220485.2014.976325
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Developing and Testing Financial Capability Education Programs Targeted to Elementary Schools

Abstract: Concerns about consumers' ability to manage their finances have triggered a range of proposals, including interventions aimed at elementary school students. The goal of these approaches is to improve lifelong economic decision making, but the evidence supporting their efficacy is thin. In this article, the authors discuss the trend toward elementary financial education and propose a framework for developing evidence-based programs. They emphasize the need for understanding the underlying mechanisms that facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…For others, these ways of thinking were relevant to all aspects of their future lives. The differentiated impact model, derived from our thematic analysis of student responses, supports the theoretical thesis on how students might be impacted by personal finance courses (Collins & Odders‐White, 2015). In this study, however, we provide additional evidence for this differential impact with data from students within finance classrooms.…”
Section: Discussionsupporting
confidence: 74%
“…For others, these ways of thinking were relevant to all aspects of their future lives. The differentiated impact model, derived from our thematic analysis of student responses, supports the theoretical thesis on how students might be impacted by personal finance courses (Collins & Odders‐White, 2015). In this study, however, we provide additional evidence for this differential impact with data from students within finance classrooms.…”
Section: Discussionsupporting
confidence: 74%
“…Lusardi et al [24] investigated young adults' status of fnancial literacy and suggested that college-educated young adults with parents having stocks and retirement savings are more likely to be fnancially knowledgeable about risk diversifcation. Targeted elementary schools, Michael Collins and Odders-White [45] developed a framework to facilitate the transformation of fnancial knowledge into the fnancial capability to make desirable decisions, and they also addressed the importance of fnancial education programs. To help improve students' ability to manage fnancial routines, a large number of fnancial institutions ofer programs or services associated with fnancial education which are accessible for students in school or college classrooms, such as programs of Hands on Banking provided by Wells Fargo, and CashCourse ofered by National Endowment for Financial Education [46].…”
Section: Financial Education and Consumer Stock Marketmentioning
confidence: 99%
“…Det understryker att sådan kunskap är nödvändig för att det ska vara möjligt att dra mer generella slutsatser om effektiviteten i olika riktade insatser och utveckla en didaktik för detta specifika kärninnehåll inom skolan (t.ex. Collins & Odders-White, 2015;Lusardi et al, 2020;Sherraden et al, 2011;Suiter & Meszaros, 2005) eller förskolan (t.ex. Roos et al, 2005).…”
Section: Forskning Om Barn Pengar Och Ekonomiunclassified